Temperature-independent genome-wide DNA methylation profile in turbot post-embryonic development. (February 2020) - Suarez-Bregua, P.; Pérez-Figueroa, A.; Hernández-Urcera, J.; Morán, P.; Rotllant, J.
Abstract: The morphological and biological characteristics of ectothermic vertebrates are known to be strongly influenced by environmental conditions, particularly temperature. Epigenetic mechanisms such as DNA methylation have been reported to contribute to the phenotypic plasticity observed in vertebrates in response to environmental changes. Additionally, DNA methylation is a dynamic process that occurs throughout vertebrate ontogeny and it has been associated with the activation and silencing of gene expression during post-embryonic development and metamorphosis. In this study, we investigated genome-wide DNA methylation profiles during turbot metamorphosis, as well as the epigenetic effects of temperature on turbot post-embryonic development. Fish growth and rates of development were greatly affected by rearing temperature. Thus, turbot raised at ambient temperature (18 °C) achieved greater body weights and progressed through development more quickly than those reared at a colder temperature (14 °C). Genome-wide DNA methylation dynamics analyzed via a methylation-sensitive amplified polymorphism (MSAP) technique were not significantly different between animals reared within the two different thermal environments. Furthermore, comparisons between phenotypically similar fish revealed that genome-wide DNA methylation profiles do not necessarily correlate with specific developmental stages in turbot. Highlights: Temperature does not affect the DNA methylation dynamics during turbot metamorphosis. Genome DNA methylation might not just be associated to metamorphosis in fish. Whole genome DNA methylation profile correlates with the chronological age in turbot.